And Was There a Boy? (A Comment on Chapter Five of “Eugene Onegin”) - Кунарев, Андрей (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The article reveals an Arzamas-Society subtext of one of Pushkin’s most famous stanzas (Eugene Onegin). The source of the lines about a boy with a sledge was ‘Nikolasha’s praise of winter pleasures’ (1783) by Alexandr Shishkov. Shishkov and his ‘children’s poem’ became one of favourite objects of mocks for the Arzamas literary society. Zhuchka is a unique word in Pushkin’s vocabulary, but it is a quote neither from a child’s language (cf. Lotman), nor from folk or country discourse (cf. Kasharnova, Stroganov): the lexeme appears in the dictionary of the Russian Academy without any stylistic label. Zhuchok, however, was Vasily Zhukovsky’s nickname, known to a narrow circle of his closest friends. Thus, the author of the paper suggests that it was the permanent Secretary of Arzamas who was placed in Shishkov’s sledge. This would make the lines in question a prime example of ‘Arzamas nonsense’.